Six-year Comparative Analysis of Licensure Examination Performance: The Case of PRMSU BLEPP Takers - Camuyong, Christian Sam F.; Adlawan, Jarele E.; Reyes, Karl Christian; Magtalas, Santi A.; Decena, Cyrem F. (South Asian Journal of Social Sciences and Humanities, 2022)
The study aimed to correlate the undergraduate General Weighted Average (GWA) and the licensure examination performances of President Ramon Magsaysay State University (PRMSU) Board Liscensure Examination for Psychologists and Psychometricial (BLEPP) takers from 2014 to 2019. Further, the study compared the results of the licensure examination based on the subject year taken. Using the quantitative research design, the licensure examination performance data were obtained from the records provided and verified by the Professionl Regulatory Commission (PRC). Meanwhile, the GWA of all the takers from 2014- 2019 were acquired from the Office of the Campus Registrar of the aforementioned University. Results had shown that the mean institutional passing rate from 2014 to 2019 is 27.33% while the overall mean of the national passing rate is 50.68% which reflects that the institution has consistent low passing rate compared to the national. Similarly, it was discovered that most test takers had difficulty on the subjects Theories of Personality and Industrial/ Organizational Psychology. Lastly, the study revealed that the undergraduate GWA showed a statistically significant positive linear correlation with the board exam performace (r = .291, p=.008).